Effect of carrier confinement on effective mass of excitons and estimation of ultralow disorder in Al x Ga1−x As/GaAs quantum wells by magneto-photoluminescence - S. Haldar (Nature Portfolio, 2017)
Abstract Effect of charge carrier confinement and ultra-low disorder acquainted in AlGaAs/GaAs multi-quantum well system is investigated via Magneto-photoluminescence spectroscopy. Significant increase of effective mass is observed for the confined exciton in narrow QWs. The foremost reason behind such an observation is due to the induced non-parabolicity in bands. Moreover, as the thickness of the QW are reduced, confined excitons in QW experience atomic irregularities at the hetero-junctions and their effects are prominent in the photoluminescence linewidth. Amount of photoluminescence line-broadening caused by the atomic irregularities at the hetero-junctions is correlated with average fluctuation (δ 1) in QW thickness. The estimated δ 1 for Al0.3Ga0.7As/GaAs QWs are found to be ±(0.14 − 1.6)× ‘one monolayer thickness of GaAs layer’. Further, the strong perturbations due to magnetic field in a system helps in realizing optical properties of exciton in QWs, where magnetic field is used as a probe to detect ultralow defects in the QW. Additionally, the influence of magnetic field on the free and bound exciton luminescence is explained by a simple model. The proposed approach for measuring the interface and volume defects in an ultra-low disordered system by Magneto-PL spectroscopy technique will be highly beneficial in high mobility devices for advanced applications.